Analysis and Design of Tapered Meander Line Antennas for Mobile Communications - Huang, Chun-Wen Paul (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Small printed antennas are becoming one of the most popular designs in personal wireless communications systems. In this paper, the characterization and design of a novel printed tapered meander line antenna are presented using the finite difference time domain technique. Experimental verifications are applied to ensure the effectiveness of the numerical model, and excellent agreement is found between numerical analysis and prototype measurements. A new design of this antenna features an operating frequency of 2.55 GHz with a 230 MHz bandwidth, which supports future generations of mobile communication systems.